Internalization routes of cell‐penetrating melanoma antigen peptides into human dendritic cells. Issue 1 (30th December 2013) - Buhl, Timo; Braun, Andrea; Forkel, Susann; Möbius, Wiebke; van Werven, Lars; Jahn, Olaf; Rezaei‐Ghaleh, Nasrollah; Zweckstetter, Markus; Mempel, Martin; Schön, Michael P.; Haenssle, Holger A.
Abstract: Optimized delivery of antigens combined with sustainable maturation of dendritic cells (DCs) is crucial for generation of effective antitumoral immune responses. Multiple approaches for ex vivo antigen loading and improvement in immunogenicity have been described. We have recently established a single‐step protocol consisting of a fusion peptide (a sequence of the melanoma antigen Melan‐A and a cationic cell‐penetrating HIV TAT domain) bound in complexes with a toll‐like receptor agonist. As the exact cellular uptake mechanisms of TAT‐coupled antigens have been a matter of considerable debate and significantly depend on cell type, cargo and concentrations, we evaluated internalization routes into human immature DCs in comparison with non‐phagocytic cell lines. We found that Melan‐A‐TAT fusion peptide uptake by DCs is mainly energy dependent, superior compared with polylysine‐coupled Melan‐A and significantly higher in DCs as compared with Jurkat cells or HUVECs. Furthermore, we could track the uptake of the fusion peptide exclusively through early endosomes to lysosome compartments after 90 min by fluorescence microscopy and immunoelectron microscopy. Specific endocytosis inhibitors revealed major internalization of the fusion peptide by DCs via clathrin‐mediated endocytosis, whereas uptake by non‐phagocytic HUVECs differed significantly, involving macropinocytosis as well as clathrin‐mediated endocytosis. As our understanding of the processes involved in internalization of TAT‐coupled cargos by human DCs broadens, and DC activation becomes available by single‐step procedures as described, further development of simultaneous DC maturation and intra‐cellular peptide targeting is warranted.